Mediação pedagógica com apoio de material didático para Educação de Jovens e Adultos - Couto, Maria Aparecida [UNESP] (2016)
In face of the results of scientific studies and based on experience reports on literacy classrooms of youth and adult education, the work related to teaching practice needs to have meaning and significance to the student. Therefore, for that purpose, it becomes necessary to realize a pedagogical meditation which is directed towards the social practices of reading and writing, considering the affective dimension in teacher-student and teaching-learning relationships. Intending to plan and propose pedagogical materials that meet the specific characteristics of young and adult learners, this research generally strives to empirically explore how has the working teacher’s mediation on youth and adult education (EJA) occurred and how it may occur, proposing a specific course material. In this direction, it presents as specific goals: a) to observe, report and analyze the context in which the mediation in three literacy classes for youth and adults occurs; b) through educators, carry the previous survey of the generative words (in alphabetical order) that have been the most worked on in their literacy classes for youth and adults; c) to produce didactic material meant for alphabetization, containing representative images of generator words, meaningful phrases, and some possible activities. Under the qualitative approach, the research was carried on in a school of youth and adults, in which thirty-eight educators and eighteen learning students took part of. It has included the following data-collecting tools: field diary meant for registering the classroom observations; appointment form for generator words, and digital image techniques for production and selection of representative photographs of the cited generator words. The obtained results, under the systematic observation of classrooms, show that the current pedagogical praxis of the schooling unit makes use of multiple methodologies, based on the historical-cultural approach, as well as the traditional one. However, it is possible to notice that the constant presence of Freire's approach, based on dialogue, affection and humanization between teachers and students, as well as the enhancement of knowledge and popular culture brought by the students upon entering school. Also as a result of the current research, this author has developed, in the in integrated product to this thesis, illustrated didactic material for the students (e-book) and containing orientations for the educators, being worth mentioning that all of said illustrations were validated by the students who took part in the present research.